Perivascular stem cells demonstrate similar stemness and chondrogenic expression potential as mesenchymal stem cells - Shan, Xiao-Long; Tunku Kamarul; Hao, Qi Daniel Looi; Jhi, Biau Foo; Raja Elina Ahmad; Sugesh Raghavan; Li, Gang; Pan, Pan Chong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Perivascular stem cells (PSCs), namely pericytes, are more accessible than traditional sources of mesenchymal stem cells (MSCs) such as bone marrow and serve as an excellent alternative cell source for treating articular cartilage damage. However, evidence of its multipotent or chondrogenic potential compared to MSCs appears lacking. The present study was thus conducted to (i) Isolate and characterize rat adipose tissue (AT)-derived and peripheral blood (PB)-derived PSC, as well as bone marrow (BM)-derived and PB-derived MSCs; (ii) Establish their multipotentiality; and (iii) Trilineage differentiation of their potentials in vitro. PSCs from AT and PB were isolated using magnetic-activated cell sorting, while MSCs were isolated from BM and PB using density gradient centrifugation. Immunophenotyping of PSCs and MSCs was analysed using flow cytometry. Trilineage differentiation of the cells was subsequently assessed using Haematoxylin– Fast Green–Safranin O staining for chondrogenesis, Alizarin Red S for osteogenesis, and Oil Red O for adipogenesis. Chondrogenesis was also analyzed by measuring the production of sulphated glycosaminoglycans. The results showed that both PSCs were similar to MSCs in expressing surface protein markers and the ability to undergo self-renewal and tri-lineage differentiation. However, PSCs expressed higher CD146 levels than MSCs. AT-PSCs exhibited the highest level of proteoglycan content, whereas the chondrogenic potential of PB-PSCs, BM-MSCs, and PB-MSCs demonstrated similar levels. Compared to MSCs, PSCs from various sources demonstrate comparable or higher chondrogenic potential, indicating that PSCs are a superior stem cell source for future cartilage injury treatment strategies.